The Concept of Justice in the Reconstruction of Legal Protection Regulations for Doctors and Patients in Health Services through Telemedicine - Rinna Dwi Lestari; Gunarto Gunarto; Sri Endah Wahyuningsih (Budapest International Research and Critics University, 2023)
Development of technology affects health services known as telemedicine. Health services through telemedicine have many benefits and high risks, so legal protection is needed. The purpose of this study is to describe, analyze and examine the regulation of legal protection for doctors and patients in health services through telemedicine has not been based on the value of justice, the obstacles to the regulation of legal protection for doctors and patients, as well as the regulation of legal protection for doctors and patients based on the value of justice Pancasila. This research method is juridical sociological, with a constructivism paradigm; the research specifications are descriptive analytical. The results of this study explain that first, the regulation of legal protection for doctors and patients in health services through telemedicine has not been based on the value of justice, because there is no legal protection that regulates considering that health services through telemedicine have a high risk. Second, the weaknesses of legal protection regulations for patients in health services by doctors through telemedicine can currently be seen from the aspects of legal substance, legal structure and legal culture. Third, the reconstruction of legal protection regulations for doctors and patients in health services through telemedicine based on the value of Pancasila justice, in terms of: aspects of legal substance can be done through strengthening legal instruments, the establishment of laws on telemedicine; then aspects of legal structure can be done through improving communication infrastructure, improving the quality and quantity of health workers, as well as synergy and understanding of health organizations and related parties. The legal culture aspect can be done through increasing the legal awareness of health workers and the public, and counseling and guidance for the public about the importance of telemedicine.